Co-culture of a Novel Fermentative Bacterium, Lucifera butyrica gen. nov. sp. nov., With the Sulfur Reducer Desulfurella amilsii for Enhanced Sulfidogenesis - Sánchez-Andrea, Irene; Florentino, Anna Patrícya; Semerel, Jeltzlin; Strepis, Nikolaos; Sousa, Diana Z.; Stams, Alfons J. M. (Frontiers in Microbiology, 2018)
Biosulfidogenesis can be used to remediate low pH and high metal content waters such as acid mine drainage and recover the present metals. The selection of a cheap electron donor for the process is important for the economic viability. In this work we isolated a novel versatile acidotolerant fermentative bacterium (strain ALET) that is able to use a great variety of substrates including glycerol. Strain ALET is an obligate anaerobe, and cells are motile, rod-shaped, spore-forming, and stain Gram-positive. Growth occurred in a pH range from 3.5 to 7 (optimum 5.5), and temperature range from 25 to 40°C (optimum 37°C). It grows by fermentation of sugars, organic acids and glycerol. It has the ability to use thiosulfate, iron and DMSO as electron acceptors. Its genome is 4.7 Mb with 5122 protein-coding sequences, and a G+C content of 46.9 mol%. Based on 16S rRNA gene sequence analysis, the closest cultured species is Propionispora hippei (91.4% 16S rRNA gene identity) from the Sporomusaceae family (Selenomonadales order, Negativicutes class, Firmicutes phylum). Based on the distinctive physiological and phylogenetic characteristics of strain ALET, a new genus and species Lucifera butyrica gen. nov., sp. nov., is proposed. The type strain is ALET (=JCM 19373T =DSM 27520T). Strain ALET is an incomplete oxidizer and acetate, among other products, accumulates during glycerol conversion. Strain ALET was used to extend the substrate range for sulfur reduction by constructing cocultures with the acetate oxidizer and sulfur reducer Desulfurella amilsii. The coculture was tested with glycerol as substrate in batch and chemostat experiments. Acetate formed by fermentation of glycerol by strain ALET resulted in sulfur reduction by D. amilsii. The coculture strategy offers good perspectives to use a wide range of cost-efficient substrates, including glycerol, to produce sulfide by specialized sulfur reducers. The recovery of heavy metals from metalliferous streams may become economically feasible by this approach.